2006
DOI: 10.1029/2005jd006103
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Radiation Measurement site atmospheric state best estimates for Atmospheric Infrared Sounder temperature and water vapor retrieval validation

Abstract: [1] The Atmospheric Infrared Sounder (AIRS) is the first of a new generation of advanced satellite-based atmospheric sounders with the capability of obtaining high-vertical resolution profiles of temperature and water vapor. The high-accuracy retrieval goals of AIRS (e.g., 1 K RMS in 1 km layers below 100 mbar for air temperature, 10% RMS in 2 km layers below 100 mbar for water vapor concentration), combined with the large temporal and spatial variability of the atmosphere and difficulties in making accurate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
317
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 282 publications
(343 citation statements)
references
References 30 publications
23
317
0
Order By: Relevance
“…The proximity recognition between the AIRS L2 atmospheric profiles and the TIGR atmospheric profiles is described in detail in . If no simultaneous AIRS L2 atmospheric profile of good quality is available (which may occur if the situation is too cloudy), a running mean average of atmospheric profiles with good quality (Tobin et al, 2006) over one week, at a spatial resolution of 1 • latitude×1 • longitude, is used. The third choice is a monthly mean of atmospheric profiles with good quality, at 1 • latitude×1 • longitude.…”
Section: Airs-lmd Cloud Property Retrieval Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proximity recognition between the AIRS L2 atmospheric profiles and the TIGR atmospheric profiles is described in detail in . If no simultaneous AIRS L2 atmospheric profile of good quality is available (which may occur if the situation is too cloudy), a running mean average of atmospheric profiles with good quality (Tobin et al, 2006) over one week, at a spatial resolution of 1 • latitude×1 • longitude, is used. The third choice is a monthly mean of atmospheric profiles with good quality, at 1 • latitude×1 • longitude.…”
Section: Airs-lmd Cloud Property Retrieval Methodsmentioning
confidence: 99%
“…These atmospheric profiles were retrieved from cloud-cleared AIRS radiances within each AMSU footprint. Validations with radiosonde data from the NOAA-NESDIS operational meteorological database archive (Divakarla et al, 2006) and with Atmospheric Radiation Measurement (ARM) data (Tobin et al, 2006) have shown that the accuracy is close to 1 K in 1 km layers for temperature and better than 15% in 2 km layers for water vapour. For the cloud property retrieval we have collocated the AIRS L2 standard products (version 5) with a subset of AIRS L1B radiance measurements which have been downloaded from the NASA data pool (http://mirador.gsfc.nasa.gov).…”
Section: Airs Datamentioning
confidence: 99%
“…We applied the VAM to a set of radiosonde profiles taken at the ARM Southern Great Plains site from July to December of 2002. These are the same data that have been used to build the "best estimate data set" in Tobin et al 6 . In particular, we analyzed the impact of the time difference between satellite and radiosonde measurements on the assessment of accuracy of the AVTP retrieval.…”
Section: Results Of Case Studymentioning
confidence: 99%
“…In practice two approaches are used to handle the issue of non-collocation 5 . Thus, in the work of Tobin et al 6 the "best estimate" radiosonde data set for the Southern Great Plains ARM site has been created. In this work the ground-based remote sensing and GOES satellite data were used to interpolate the original radiosonde measurements to correct for time and space differences between sondes and AIRS overpasses.…”
Section: {(∆ -(X -R(x))(∆ -(X -R(x)) }mentioning
confidence: 99%
“…state vector or retrievals) (Tobin et al 2006, Pougatchev et al 2009, Larar et al 2010. For example, Tobin et al (2006) used a multi-instrument/platform correlative measurement dataset to build the bestestimated atmospheric state for each individual satellite measurement for validation.…”
Section: Introductionmentioning
confidence: 99%